The Role Of The Government In Empowering Alternative Economies For Cap Tikus Producers In Kumelembuai Village, South Minahasa Regency - Pangkey, Itje; I.R. Rantung, Margareth; Hapsari, Nimas (Iapa Proceedings Conference, 2025)
This study examines the role of government in supporting alternative economic empowerment for Cap Tikus producers in Kumelembuai Village, North Sulawesi. Cap Tikus, a traditional alcoholic beverage made from palm sap, is a key source of income and cultural identity for the local community. However, heavy dependence on its production and the agricultural sector exposes villagers to economic risks. Through a review of current conditions and literature, this research highlights the need for economic diversification to improve community resilience and welfare. The study emphasizes the importance of government intervention—such as training, capital support, and market access—in facilitating sustainable economic development. Findings aim to inform policy strategies that strengthen local economies and reduce reliance on a single income source.